The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1159/000347024
|View full text |Cite
|
Sign up to set email alerts
|

Steroid Withdrawal in Pediatric Kidney Transplant Allows Better Growth, Lipids and Body Composition: A Randomized Controlled Trial

Abstract: Background: Glucocorticoid immunosuppressant therapy in pediatric kidney transplant (Tx) recipients does not allow the improvement of growth after Tx. Objective: To determine the effect of early steroid withdrawal (SW) on longitudinal growth, insulin sensitivity (IS), and body composition (BC). Methods: This was a prospective, randomized, multicenter study in Tx. Insulin-like growth factor (IGF)-I, IGF-binding protein 3 (IGFBP3), IS, and BC (DEXA/pQCT) were determined at baseline and up to 12 months after Tx. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
1
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(35 citation statements)
references
References 29 publications
1
32
1
1
Order By: Relevance
“…8 However, post transplant, the steroidal therapy often included in immunosuppression regimens can affect longitudinal growth and calcium/ phosphorous metabolism. 9,10 Aetiology, pathology and prognosis…”
Section: Clinical Effectiveness Systematic Reviewmentioning
confidence: 99%
“…8 However, post transplant, the steroidal therapy often included in immunosuppression regimens can affect longitudinal growth and calcium/ phosphorous metabolism. 9,10 Aetiology, pathology and prognosis…”
Section: Clinical Effectiveness Systematic Reviewmentioning
confidence: 99%
“…[1][2][3][4] Glucocorticoid reduction/withdrawal is one of the most important issues for successful long-term immunosuppressive therapy in renal transplantation. [5][6][7][8] However, glucocorticoids need to be restarted to prevent the worsening of renal function because of occurrence of acute rejection episodes in some patients or in patients who experience glucocorticoid withdrawal syndrome. [9][10][11] Increasing the dose of the immunosuppressive drugs could also result in a variety of side effects that plague the patients.…”
Section: Introductionmentioning
confidence: 99%
“…This study, using DXA to examine bone mineral density after transplantation, reported no change in lean mass in 9 children at 6 months after transplant 72 . In contrast, lean mass and fat mass both increased at 12 months after renal transplantation in 30 children; with greater total body and trunk fat in those who remained on steroids compared to those who stopped steroids after 6 days 67 . Improvement in fat free mass, but no change in fat mass was noted on longitudinal DXA scanning in 41 children at 24 months after lung transplantation 73 .…”
Section: Specificmentioning
confidence: 88%
“…The role of immunosuppression in the development of obesity was proposed in an editorial in 2008 discussing whether children after liver transplant were more prone to non-alcoholic fatty liver disease 119 . Several studies have implicated steroids as the cause for reduced body cell mass and increased fat mass after renal transplantation 66,67 . The use of steroids immediately post-transplant is almost universal for all solid organs and by all centres.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation